2013
DOI: 10.1186/1475-2867-13-19
|View full text |Cite
|
Sign up to set email alerts
|

EGCG induces human mesothelioma cell death by inducing reactive oxygen species and autophagy

Abstract: Malignant mesothelioma is an asbestos-related fatal disease with no effective cure. We studied whether a green tea polyphenol, epigallocathechin-3-gallate (EGCG), could induce cell death in five human mesothelioma cell lines. We found that EGCG induced apoptosis in all five mesothelioma cell lines in a dose-dependent manner. We further clarified the cell killing mechanism. EGCG induced reactive oxygen species (ROS), and impaired the mitochondrial membrane potential. As treatment with ROS scavengers, catalase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 37 publications
2
43
3
1
Order By: Relevance
“…Interestingly; the observed increase in proliferation inhibition was not associated with apoptosis induction. These observations are in contrast with some published studies, which show an association between autophagy inhibition and enhanced apoptosis [33, 53]. On the other hand, our results suggest that autophagy inhibition synergizes with Nx (to prevent autophagy activation) resulting in enhanced proliferation inhibition rather than apoptosis activation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly; the observed increase in proliferation inhibition was not associated with apoptosis induction. These observations are in contrast with some published studies, which show an association between autophagy inhibition and enhanced apoptosis [33, 53]. On the other hand, our results suggest that autophagy inhibition synergizes with Nx (to prevent autophagy activation) resulting in enhanced proliferation inhibition rather than apoptosis activation.…”
Section: Discussioncontrasting
confidence: 99%
“…It is well established that autophagy and ROS can facilitate cell death or cell survival depending on the nature of stimuli and cellular context [6, 53]. Given our observation of reduced intracellular ROS levels upon autophagy inhibition, we tested the impact of autophagy on Nx induced anti-proliferative activities.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that a high concentration (50 -100 M) of EGCG stimulates autophagy leading to cell death in cancer cells (44,45). Another study reported that EGCG stimulates autophagy, which leads to inhibition of endotoxin-induced septic shock through EGCG-induced degradation of HMGB1, a late lethal inflammatory factor (46).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) were reported to be responsible for EGCG-induced apoptosis in mesothelioma (27) and EGCG-induced ROS production in endometrial carcinoma cells (28). However, ROS were not involved in EGCG-induced apoptosis in human laryngeal epidermoid carcinoma (Hep2) cells (14), although EGCG reduced deoxynivalenol-induced ROS in HT-29 cells (29).…”
Section: Discussionmentioning
confidence: 99%